2003
DOI: 10.1211/002235703322277186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berberine on proliferation, cell cycle and apoptosis in HeLa and L1210 cells

Abstract: Previous studies on the anticancer activity of protoberberine alkaloids against a variety of cancer cell lines were extended to human tumour HeLa and murine leukemia L1210 cell lines. An attempt was also made to investigate the relationship between the cytotoxic activity of berberine and its molecular mechanism of action. Cytotoxicity was measured in-vitro using a primary biochemical screening according to Oyama and Eagle, and the growth inhibition assay. The in-vitro cytotoxic techniques were complemented by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(77 citation statements)
references
References 33 publications
7
67
0
3
Order By: Relevance
“…In the present study, 10-20 µM of berberine significantly induced G1 arrest in CCA cells in dose and time dependent fashions. The induction of cell cycle arrest at G1 phase by low doses of berberine (<50 µM) were demonstrated in several cancer cell lines including human bladder cancer cells, 22) a murine leukemia cell line 23) and a non-Ov-associated CCA cell line. 15) In addition, high doses of berberine (>50 µM) promoted G2/M arrest or induction of apoptosis as reported in many human cancer cells, e.g., gastric cancer 24) and prostate cancer.…”
Section: )mentioning
confidence: 99%
“…In the present study, 10-20 µM of berberine significantly induced G1 arrest in CCA cells in dose and time dependent fashions. The induction of cell cycle arrest at G1 phase by low doses of berberine (<50 µM) were demonstrated in several cancer cell lines including human bladder cancer cells, 22) a murine leukemia cell line 23) and a non-Ov-associated CCA cell line. 15) In addition, high doses of berberine (>50 µM) promoted G2/M arrest or induction of apoptosis as reported in many human cancer cells, e.g., gastric cancer 24) and prostate cancer.…”
Section: )mentioning
confidence: 99%
“…Berberine has been reported to induce apoptosis through a mitochondrial pathway that includes upregulation of p53, alterations in Bcl-2/Bax ratios, a decrease in mitochondrial membrane potential, release of cytochrome c, and activation of caspases [2,[6][7][8][9][10][11][12]. This is of particular interest in light of studies demonstrating a mitochondrial localization of berberine, raising the possibility that apoptosis results from mitochondrial damage induced by berberine.…”
Section: Introductionmentioning
confidence: 99%
“…A report from Ko et al demonstrated that berberine has vasorelaxant and anti-proliferative effects on vascular SMCs [21]. In addition, Jantova et al had disclosed that berberine could cause G1/0 arrest in cancer cell lines [22]. Recently, Lee et al reported that berberine could inhibit SMC growth and inhibit Akt activation after angiotensin II stimulation [23].…”
Section: Introductionmentioning
confidence: 99%